ETHNOMATHEMATICS: MUSICAL INSTRUMEN IN JA'I DANCES FOR CULTURALLY RESPONSIVE TEACHING IN ELEMENTARY SCHOOLS - Bito, Gregorius Sebo; fredy, fredy (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
In cultural responsive learning, teachers need to have the ability to explore mathematical phenomena in cultural elements as learning content. This research is a qualitative descriptive study aimed at exploring ethnomathematics in Bajawa traditional dances, namely the Ja,i dance, its relevance to competency standards and basic mathematics competencies in elementary schools. The approach used is ethnographic. The technique used is observation and study of documents and the researcher himself acts as the main instrument. Observations were made on the accompanying music devices contained mathematical concepts. Furthermore, researchers compare with the basic competencies of elementary school mathematics. The results showed mathematical material was found in the musical instrument section of Ja,i dance. The surface of the gong and the drum (gendang) are circular, the body of the large drum is frustum of a cone, and the gendang laba kagu, laba bhuga and gong are tube-shaped. In the middle of the gong there is a kind of lump which is shaped like a half ball. The implementation of this research can be applied in cultural responsive learning in elementary schools.Keywords:Â ethnomathematics, learning, cultural responsive, jai,i dance